Influence of intracanal medication with calcium hydroxide paste in the penetration of the shutter cement - Veintimilla Lozada, Virginia Natalia (2019)
The elimination of calcium hydroxide in the root canal is decisive for the success of endodontic treatment, the remnants can interact negatively with endodontic sealants increasing filtrations and decreasing the quality of the seal. Objective: To evaluate the effect of intra-duct medication with calcium hydroxide paste on the penetration of the sealing cement inside the dentinal tubules. Materials and methods: 20 distal roots of upper molars were instrumented using the Wave One Large 40 / .08 System. They were randomly divided into two groups: one sealed with a single cone technique and Ah plus cement with rhodamine-B and another sealed with the same technique and Ah plus cement with rhodamine B, previous placement for 15 days and removal by recapping the paste calcium hydroxide. Subsequently, the teeth were cut transversely and photomicrographs of the cervical, middle and apical third were performed using the laser scanning confocal microscopy technique. The maximum depth of penetration was determined through the Image J program. Results: The Ah plus sealing cement had lower penetration values when the calcium hydroxide paste was previously used as an intra-channel medication (p <0.01). The third of the duct with the highest penetration was the cervical third followed by the middle third and finally the apical (p <0.01). Conclusion: Remaining calcium hydroxide decreases the penetration of the sealing cement Ah plus in the dentinal tubules in all thirds of the root canal.